2016
DOI: 10.1186/s12870-016-0872-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel Glycine soja homeodomain-leucine zipper (HD-Zip) I gene, Gshdz4, positively regulates bicarbonate tolerance and responds to osmotic stress in Arabidopsis

Abstract: BackgroundWild soybean (Glycine soja) is a highly adaptive plant species which can grow well in saline-alkaline soils. In soybean genome, there exist about 140 HD-Zip (Homeodomain-leucine Zipper) genes. HD-Zip transcription factor family is one of the largest plant specific superfamilies and plays important roles in response to abiotic stresses. Although HD-Zip transcription factors have been broadly reported to be involved in plant resistance to abiotic stresses like salt and drought, their roles in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Overexpression of a G. soja ethylene‐responsive factor GsERF6 increased Arabidopsis tolerance to HCO 3 − rather than high pH (Yu et al ). Similarly, another transcription factor Gshdz4 was as well found to regulate bicarbonate stress in Arabidopsis (Cao et al ). In our present work, we showed that GsSLAH3 OX plants had more open and green leaves at germination stage and generated longer roots at seedling stage than WT under KHCO 3 treatment (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Overexpression of a G. soja ethylene‐responsive factor GsERF6 increased Arabidopsis tolerance to HCO 3 − rather than high pH (Yu et al ). Similarly, another transcription factor Gshdz4 was as well found to regulate bicarbonate stress in Arabidopsis (Cao et al ). In our present work, we showed that GsSLAH3 OX plants had more open and green leaves at germination stage and generated longer roots at seedling stage than WT under KHCO 3 treatment (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…After washing, the seeds were sowed in soil for germination at 24–26 °C for 20 days in 16‐hr light/8‐hr dark cycles. Every 10 seedlings were treated with dark (6 hr), 50 mM NaHCO 3 (pH 8.5; 12 hr), 200 mM NaCl (12 hr), cold (0 °C for 24 hr), drought (air dry for 4 hr), and ABA (0.1 mM for 24 hr), respectively, according to the described (Cao et al, ). Tobacco ( Nicotiana benthamiana ) and Arabidopsis seeds were directly sowed in soil and grown at 24–26 °C in 16‐hr light/8‐hr dark cycles till for transient infection of agrobacteria and protoplast preparation.…”
Section: Methodsmentioning
confidence: 99%
“…The whole genome of G. soja has been sequenced and one novel gene ( GmCHX1 ) related with abiotic stresses was identified by comparative genomics (Qi et al, ). Nevertheless, we also reported a dozen of wild soybean genes with resistance to abiotic stresses in plants (Cao et al, , ; Duanmu et al, ; Jia et al, ; Yu et al, , ). However, the functions of SnRK1 kinases (defined as GsSnRK1s) in wild soybean are still largely unknown.…”
Section: Introductionmentioning
confidence: 94%
“…After the discovery of HD‐Zip proteins in 1991 by Ruberti et al , many HD‐Zip encoding genes had been identified and isolated from A. thaliana and other species such as sunflower , tomato ( Lycopersicum esculentum ) , carrot ( Daucus carota ) , cucumber ( Cucumis sativus ) , cotton ( Gossypium sp) and rice ( O. sativa ) , among others .…”
Section: Biological Functions Of Hd‐zip I Tfsmentioning
confidence: 99%